Intersection of main James abacus diagram for the outer chain movement with length [1, 0, 0…] - Mohommed, Eman F.; Ahmad, Nazihah; Ibrahim, Haslinda (Universiti Teknikal Malaysia Melaka, 2016)
James abacus with β- number is one of the graphical representations for any partition of a non-negative integer.James abacus can be divided into several chains which consist of outer and inner chains. In this paper, a new diagram A tco is developed by employing movement to the outer chain with length [1, 0, 0,…] on the active James abacus.Then, a consecutive new diagram of b1, b2…, be-1 can be found from active diagram A tco .Finally intersection of the main new diagrams A tco is obtained. Some theoretical results for intersection of main James diagram are established.In addition, several examples are given to illustrate the results